Rebranding Produk Sebagai Pengembangan Pemasaran Keripik Tempe Al Barokah - Ashari, Riza; Hidayatullah, Muhammad Iqbal; Yahya, Ahmad Bimo Wiranata; Abdillah , Akbar; Wardana, Aditya Dyo; Yahya, Habibillah; Churaez, Wildan Maududy; Thoriqunnajih, Thoriqunnajih; Hilmi, Zaim; Arsyad, Hifni Bik Nasif; Kurdi, Sadam; Wibowo, Teguh Laksono (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to enhance the competitiveness of Al Barokah Tempe Chips through a rebranding strategy. The focus of the activities includes redesigning the logo and packaging, adding new flavor variants, and registering Intellectual Property Rights (IPR). The method used is a participatory and collaborative approach involving KKN students, business actors, and the community. The results show that rebranding the logo and packaging successfully created a stronger and more attractive visual identity. The addition of a new balado flavor received positive responses from the community, while the IPR registration is ongoing as an effort to protect the brand. These findings indicate that rebranding can enhance product appeal and open up broader market opportunities. This research provides significant contributions to the development of SMEs, particularly in branding and marketing local products.